2015
DOI: 10.1620/tjem.236.193
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sclerosing Sialadenitis of the Submandibular Gland as the Initial Symptom of IgG4-Related Disease: A Case Report

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a systemic condition accompanied by tumefactive lesions, dense lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells, storiform fibrosis in various organs, and, frequently, elevated serum IgG4 levels. Chronic sclerosing sialadenitis (also termed Küttner's tumor) is thought to be a lesion of IgG4-RD; thus, IgG4-related sialadenitis may be the initial symptom of IgG4-RD. We herein report a 64-year-old Japanese female with IgG4-related chronic sclerosing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…15 IgG4-RD often affects multiple organ systems, most typically causing sialadenitis, pancreatitis, and/or lymphadenopathy. 6,16,26 Common findings in IgG4-RD include an elevated serum IgG4 level (with a ratio of IgG4/IgG greater than 40%), infiltration of organs with IgG4-positive plasma cells, and fibrosis of the affected organs. 6,7,16 In the presented case, the patient’s IgG4 IHC staining was on the lower end of the results reported in other cases affecting the CNS, at 10 cells/hpf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 IgG4-RD often affects multiple organ systems, most typically causing sialadenitis, pancreatitis, and/or lymphadenopathy. 6,16,26 Common findings in IgG4-RD include an elevated serum IgG4 level (with a ratio of IgG4/IgG greater than 40%), infiltration of organs with IgG4-positive plasma cells, and fibrosis of the affected organs. 6,7,16 In the presented case, the patient’s IgG4 IHC staining was on the lower end of the results reported in other cases affecting the CNS, at 10 cells/hpf.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are case reports in which masses that have the radiological appearance of cancerous tumors are subsequently biopsied and demonstrate no malignant cells, instead showing the histopathological characteristics consistent with IgG4-RD. 20,26 These lymphoplasmacytic lesions tend to affect solid organs such as the pancreas, thyroid, lung, and kidney. 1,13,26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 12 articles, 3 were duplicates. Review of these 9 articles found one additional article fulfilling inclusion criteria, leading to a final sample size of 10 articles …”
Section: Case Reportmentioning
confidence: 99%